Walter Lorenz - Social Work - Central and Eastern European Countries - Oldřich Chytil (Social Work & Society, 2007)
As president of the European Centre for Community Education - ECCE it is a great pleasure for me and a special honour to contribute (in the form of an epilogue) to the Festschrift which is published and dedicated to Walter Lorenz on the occasion of his sixtieth birthday. I would like to mention and stress the fact that this Festschrift has only been made possible through the cooperation of ECCE and the online-only journal "Social Work &Society", a journal which is open to and free of charge accessible by the whole scientific and professional community all over Europe and in the rest of the world.